Antifungal Activities of Selected Medicinal Plant Crude Extracts on Pathogenic Fungi, Colletotrichum Capsici and Colletotrichum Gloeosporioides - Johnny, Lucy (2011)
The antifungal activities of the leaves extract of 15 selected medicinal plants; Alpinia galanga (L.) Willd., Alstonia spatulata Blume., Annona muricata L., Blechnum orientale L., Blumea balsamifera L., Centella asiatica L., Dicranopteris linearis (Burm. f.) Underw., Dillenia suffruticosa (Griff ex Hook.f. & Thomson) Martelli, Litsea garciae Vidal., Melastoma malabathricum L., Momordica charantia L., Nephrolepis biserrata (Sw.)., Pangium edule Reinw., Piper betle L., and Polygonum minus Huds., were evaluated on plant pathogenic fungi; C. capsici and C. gloeosporioides. C. capsici was isolated from chili, and C. gloeosporioides was isolated from mango. Different antifungal assays were employed in this study viz Agar-disc dilution assay to determine the inhibition of radial growth, dry mycelial weight assay to determine the inhibition of aerial growth, determination of Minimum Inhibition Concentration (MIC), and the rate of sporulation assay. The antifungal assays were carried out in five different treatments; which were distilled water as negative control, crude extract of leaves in methanol, chloroform, acetone and Kocide 101 and Benomyl as positive control. Seven species namely P. betle, A. galanga, C. asiatica, M. charantia, B. balsamifera, P. minus, and D. suffruticosa were effective in inhibiting the growth of C. capsici at various concentrations. The methanol, chloroform and acetone leaf crude extracts of P. betle in all concentration were found to be the most effective in inhibiting the radial growth, aerial growth, and sporulation of C. capsici. Overall, the methanol leaf crude extract of P. betle in 10 μg/mL showed the highest percentage in inhibiting the radial growth (85.25%), aerial growth (82.21%), and sporulation (80.93%) of C. capsici. The exact concentrations of P. betle that fully inhibited the growth of C. capsici (MICs) were 12.50 mg/mL in methanol, 17.50 mg/mL in chloroform, and 15.00 mg/mL in acetone. On the other hand, 4 species namely A. galanga, P. betle, M. malabathricum, and B. balsamifera were effective in inhibiting the growth of C. gloeosporioides at various concentrations. The methanol, chloroform and acetone leaf crude extracts of A. galanga in all concentration (except for 0.01 μg/mL of chloroform and acetone extracts) were found to be the most effective in inhibiting the radial growth, aerial growth, and sporulation of C. gloeosporioides. Overall, the methanol leaf crude extract of A. galanga in 10 μg/mL showed the highest percentage in inhibiting the radial growth (66.39%), aerial growth (68.21%), and sporulation (68.89%) of C. gloeosporioides. The exact concentrations of A. galanga that fully inhibited the growth of C. gloeosporioides (MICs) were 15.00 mg/mL in methanol, 17.50 mg/mL in chloroform, and 17.50 mg/mL in acetone. As a conclusion, the leaf crude extracts that exhibited effectiveness by showing more than 50% inhibition against C. capsici and C. gloeosporioides should be considered for further evaluation; with P. betle and A. galanga leaf crude extracts being the most effective in inhibiting the fungi respectively and thus, exhibited highest potential as new leading biofungicides in agriculture.